The Contribution of Learning Motivation, Self-Control, and Parenting Styles to Students’ Outcomes in Islamic Religious Education - Dinda Dwi Azizah; Ahmad Sabri; Juliana Batubara; Berillya Imandika (Cakrawala : Jurnal Kajian Manajemen Pendidikan Islam dan Studi Sosial, 2026)
This study is motivated by low learning motivation, weak self-control, and limited parental support, which affect students’ learning outcomes in Islamic Religious Education (PAI). Preliminary data show that only 48% of students actively participate in discussions, 58% delay completing assignments, 60% submit assignments late, 65% report insufficient parental support, and 40% experience pressure due to authoritarian parenting. This study aims to examine the partial and simultaneous contributions of learning motivation, self-control, and parenting styles to the learning outcomes of Grade XI Phase F students at SMAN 5 Padang. It uses a quantitative approach with an ex post facto method. The population consists of 431 students, with a sample of 207 selected through proportional stratified random sampling. Data were collected using Likert-scale questionnaires and analyzed using simple and multiple linear regression. The results show that learning motivation contributes 87.6%, self-control 6.4%, parenting style 44%, and all variables simultaneously 95.7% to learning outcomes. It is concluded that these variables have a significant effect, highlighting the need for integrated efforts to enhance motivation, strengthen self-control, and promote positive parenting to optimize PAI learning outcomes.